Structural elements and performance of entrepreneurial management systems at large corporations - Irina N. Tkachenko; Marina A. Meteleva (Управленец)
The Russian economy is currently lagging behind developed nations in terms of innovation, which necessitates adopting relevant approaches to managing socio-economic systems to keep them competitive and ensure their sustainable develop ment. Large corporations have significant resource potential and social power, which makes it relevant to improve management of their entrepreneurial activity that stimulates innovation development. The paper aims to judge the quality of entrepreneurial management systems at large corporations and evaluate their innovation performance. Corporate governance theory and man agement theory constitute the methodological framework of the study. The research methods used are qualitative, regression and comparative analysis. The empirical data are obtained from 160 corporations included in 2023 RAEX-600 Ranking and rep resenting 21 industrial sectors, as well as data from the RF Federal State Statistics Service and the All-Russia data system on com panies and business “For Honest Business” for the period of 2010–2022. The study identifies 19 elements of the entrepreneurial management system at large corporations, e.g., the presence of an R&D center, startup support, commitment to open innovation, a corporate venture fund, etc., and assesses how intensively they are used across industries. As for the innovation performance of the system under review, no statistical relationship was observed between performance indicators of many corporations and the volume of shipped innovative products. Thus, the research reveals that entrepreneurial management systems at a large number of corporations lack innovation performance, which requires further research into their quality.